Controlled vocabulary dictionary for UAV, phenotyping and image data annotation - CGIAR Research Program on Rice (2019)
The controlled vocabularies for UAVs, phenotyping and imagery have been developed and piloted with IRRI's drone data trials, however still further development is required for these to move to the uptake rom next users.